UPAYA MENINGKATKAN COMPETENCE WRITING MELALUI MODEL PEMBELAJARAN KONSEP KALIMAT SISWA KELAS VII B SEMESTER GENAP SMP NEGERI 2 AMBULU - Endang Sri Lestari (Education Journal : Journal Educational Research and Development, 2018)
This study serves to improve students' ability in writing competence, which proved results. Based on the results of research conducted by class VII B with the number of men 17 students and 20 women showed an increase in writing competency through learning model of sentence concept by students. These improvements can be seen in the results of learning activities that increase from cycle I to cycle II. Students score I cycle average 72,84 to 77,70 in cycle II. The above group increased cadence 18,92%, from cycle 1 was 62,16% to silkus 2 was 81,08%